Ultra-wideband diamond-shaped metamaterial absorber for radar cross section reduction - Defrianto Defrianto; Erwin Kurnia; Saktioto Saktioto; Tengku Emrinaldi; Feby Nur Sakinah; M Ikhsan; Vepy Asyana; Yan Soerbakti (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2026)
This study presents the design and full-wave simulation of a diamond-shaped metamaterial absorber configured in a 4×4 array for applications in radar cross section reduction (RCSR). The structure was modeled on an FR-4 substrate with a copper patch and metallic ground plane to achieve high absorption across the ultra-wideband (UWB) frequency range of 0.09 – 10 GHz. Simulations were conducted using CST Studio Suite. Key radar-related performance parameters including reflection (S11), transmission (S21), and absorption were analyzed. Results indicate that the absorber achieves extremely low reflection values (return loss up to -85 dB), near-zero transmission due to the ground plane, and absorption exceeding 80% in targeted radar bands. These findings demonstrate the high potential of diamond-shaped metamaterial absorbers for stealth applications and electromagnetic wave attenuation in modern radar systems.